Pengaruh Kepemilikan Manajerial, Institusional, Asing dan Keluarga Terhadap Kinerja Keuangan Sektor Property yang Terdaftar di Bursa Efek Indonesia 2013-2022 - Apriana Pratiwi Andini; Utomo, Rochmad Bayu (Economic Reviews Journal, 2024)
This study aims to analyze the effect of managerial ownership, institutional ownership, foreign ownership, and family ownership on the financial performance of property sector companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2022. This research is quantitative, utilizing statistical analysis to test the influence of each independent variable on financial performance. The population of the study consists of all property, real estate, and building construction companies listed on the IDX, with a purposive sampling technique applied based on specific criteria. Secondary data were obtained from annual reports published by companies that meet the study criteria. The analysis results indicate that managerial, institutional, foreign, and family ownership significantly affect the financial performance of property sector companies. These findings contribute important insights into how ownership structures can influence financial performance in Indonesia's property sector.